Mentoring Pengelolaan Website DSP3A: Meningkatkan Kinerja Berbasis Internet - yuliana, Yuliana; Cahyaningtyas, Christian; Thomas, Santi; Manggara, Angga Domeos (STMIK Royal, 2025)
The future of the internet is the main destination for connecting people with ideas and information. Through the technology sector, which is growing rapidly, it plays an important role in increasing the progress of a region. Various platforms work together to change the way humans interact through website technology which is the fastest and widest media in presenting and accommodating information. Government institutions, namely DSP3A, really need this technology, in addition to functioning as a promotional media, displaying institutional profiles and accommodating institutional activities. The method applied is through direct socialization and training to admins. The purpose of this service is to mentor the admin, one of the service devices that still has minimal knowledge about web management, totaling 4 people. The results of the mentoring are Mentoring for Admins/Operators, Explanation of Website Functions, Introduction to WordPress Dashboard Features, Collecting and preparing Data and Information for use in creating Social Media Content, Introduction to Manual Books as Learning Modules in using the WordPress Dashboard. Introduction and explanation of Cpanel and Hpanel.Keywords: company profile; CMS wordpress; internet; mentoring; website Abstrak: Masa depan internet menjadi tujuan utama untuk menghubungkan orang dengan ide dan informasi. Melalui sektor teknologi yang pertumbuhannya semakin berkembang pesat, sehingga menjadi peran penting untuk meningkatkan kemajuan suatu daerah. Berbagai platform saling bekerja sama untuk mengubah cara manusia berinteraksi melalui melalui Teknologi website yang merupakan media tercepat dan terluas dalam menyaji dan menampung informasi. Lembaga pemerintah yaitu DSP3A sangat membutuhkan teknologi tersebut, selain berfungsi sebagai media promosi, menampilkan profil lembaga dan menampung kegiatan lembaga. Adapun metode yang diterapkan adalah dengan sosialisasi dan pelatihan kepada admin secara langsung. Tujuan pengabdian ini adalah melakukan mentoring kepada admin, salah satu perangkat dinas yang masih minim pengetahuan tentang pengelolaan web berjumlah 4 orang. Hasil mentoring adalah Pendampingan kepada Admin/Operator, Pemaparan Fungsi Website, Pengenalan Fitur Dashboard wordpress, Mengumpulkan dan mempersiapkan Data dan Informasi untuk digunakan dalam pembuatan Konten Sosial Media, Pengenalan Manual Book sebagai Modul Pembelajaran dalam penggunaaan Dashboard Wordpress. Pengenalan dan penjelasan Cpanel dan Hpanel.Kata kunci: company profile; CMS wordpress; internet; mentoring; website